Pengaruh model project citizen dengan pendekatan saintifik terhadap penguasaan kompetensi kewarganegaraan dalam pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Mulyoto, Galih Puji; Samsuri, Samsuri (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This study was aimed at determining the effect of applying a project citizen model with the scientific approach in learning PPKn the mastery of civic competencies. This study uses a quantitative approach with a quasi-experimental research methods. Data collection technique were test, questionnaire and observation. Data were analyzed using t test and Gain Score. The results showed that there is significant influence implementation of the project citizen model with the scientific approach to learning PPKn the mastery of civic competencies compared using problem-based learning model with a scientific approach. It is shown results posttest control group and experiment to 7.182> 2.000 ttabel. In every dimension of civic competencies also shows the results of a significant difference, namely: civic knowledge (to 6.088> 2.000 ttable), civic skills (to 2,554> ttable 2.000), civic attitude (to 2,055> ttable 2.000). Analysis Gain score in the experimental class showed 0.38 results in the category of "moderate", while the control group showed 0.15 results in the category of "low".